2018
DOI: 10.1111/dom.13422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of once‐weekly semaglutide on the counterregulatory response to hypoglycaemia in people with type 2 diabetes: A randomized, placebo‐controlled, double‐blind, crossover trial

Abstract: AimsTo investigate the effects of semaglutide vs placebo on glucagon and other counterregulatory hormones during hypoglycaemia in type 2 diabetes (T2D).MethodsIn this double‐blind, placebo‐controlled, single‐centre trial, we randomized 38 men and women (treated only with metformin) 1:1 to 2 12‐week crossover periods of once‐weekly subcutaneous semaglutide or placebo, each followed by a hypoglycaemic clamp procedure. The primary endpoint was change in glucagon concentration from target plasma glucose (PG) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, since GLP-1RA mainly lower blood glucose by stimulating glucose-dependent insulin secretion, hypoglycemia is an infrequent problem. In addition, the inhibition of glucagon release does not occur under hypoglycemic conditions ( 35 ). In SUSTAIN-6, severe or plasma glucose-confirmed (<56 mg/dl [3.1 mol/L]) hypoglycemia occurred in similar rates between patients with semaglutide (23.1% in the 0.5 mg group and 21.7% in the 1 mg group) and placebo (21.2%) ( 28 ).…”
Section: Adverse Effects Of Semaglutidementioning
confidence: 99%
“…However, since GLP-1RA mainly lower blood glucose by stimulating glucose-dependent insulin secretion, hypoglycemia is an infrequent problem. In addition, the inhibition of glucagon release does not occur under hypoglycemic conditions ( 35 ). In SUSTAIN-6, severe or plasma glucose-confirmed (<56 mg/dl [3.1 mol/L]) hypoglycemia occurred in similar rates between patients with semaglutide (23.1% in the 0.5 mg group and 21.7% in the 1 mg group) and placebo (21.2%) ( 28 ).…”
Section: Adverse Effects Of Semaglutidementioning
confidence: 99%
“…As for exogenous administration of GLP-1 RA, several studies have shown suppression of glucagon secretion vs placebo during normo-and hyperglycemia, particularly in the postprandial state (28,31,32). A glucose dependency of this effect is supported by studies in which no GLP-1 RA-mediated suppression of glucagon could be seen in during hypoglycemic, but in some cases also normoglycemic, clamps (33,34,35,36). However, suppression of glucagon secretion during mild hypoglycemia (glucose 3.2-5.0 mmol/L) that was not evident during more pronounced hypoglycemia (glucose <3.0 mmol/L) have also been reported in some studies (22,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Semaglutide demonstrated improved glycaemic control and decreased body weight with a safety profile similar to other GLP-1 Receptor Agonists (GLP-1RAs) [63]. Nevertheless, we noted an increased incidence of nausea, vomiting, and diarrhea.…”
Section: Liraglutidementioning
confidence: 48%